Staged upper and lower lip reanimation following facial palsy: Peer-reviewed, patient-rated and objective outcomes. Issue 6 (June 2022) - Mabvuure, Nigel Tapiwa; Pinto-Lopes, Rui; Bolton, Lauren; Tzafetta, Kallirroi
Abstract : Background: One approach to reanimating both upper and lower lips following facial palsy is through staged surgery: cross-face nerve grafting at stage I, free gracilis muscle transfer to levators at stage II and pedicled anterior belly of digastric muscle transfer (ABDMT) to depressors at stage III. The results of this approach were hitherto unquantified. Methods: This study retrospectively assessed peer-reviewed, patient-rated and objective outcomes following staged reanimation in adults between 2010 and 2020. Demographics, palsy characteristics and surgery details were recorded. Pre- and postoperative videos were rated by independent assessors using Terzis' aesthetic and symmetry scale. Photographs were analysed using Emotrics and patients completed the Glasgow Benefit Inventory (GBI) patient-rated outcome measure. Results: Ten patients [mean age = 34 (SD = 12.48)] were eligible. All regained lip elevation and depression. All markers of symmetry improved after gracilis transfer. All markers were also improved after ABDMT except for lower lip height when smiling with teeth showing ( p > 0.05). Five patients (50%) responded to the GBI (mean score = +39.44). No patients reported detriment from the reanimations. Mean Terzis' scores preoperatively and after stages II and III were 1.5, 2.26 and 2.39, respectively ( p < 0.05). Nine patients underwent aesthetic refinements [lipofilling to lower lip notches ( n = 5), debulking of gracilis bulk ( n = 6), repositioning of muscle insertion ( n = 5) and facelifts ( n = 2)]. Conclusion: The outcomes were positive objectively and as judged by peers and patients themselves. Aesthetic refinements may also be required to enhance these results.